Infected omental cyst complicated with subacute intestinal obstruction and ileal erosion in a 2-year-old boy: A case report - Hock Chin Chong; Hazlina Mohd Khalid; Nur Atiqah Mohd Hanifah; Vebster Jaffrey; Naveena Thiyagaraja; Firdaus Hayati (Pan African Medical Journal, 2021)
An omental cyst is a rare intraabdominal pathology that can cause acute abdomen and intestinal obstruction among children. A 2-year-old boy presented with fever, bilious vomiting, abdomen distension and loose stool of acute onset. The chest and abdominal radiographs showed right pleural effusion and prominent small bowels with thickening walls respectively. Ultrasonography revealed a gastrointestinal duplication cyst. An exploratory laparotomy was done and found a 5x5 cm infected omental cyst, severely adhered to and eroded into the ileum causing a small perforation. Omental cyst excision and ileal primary repair were done. The final diagnosis was a benign omental cyst. Omental cyst is usually asymptomatic; however, symptomatic omental cyst should be cautious for bleeding, intestinal obstruction, infection, torsion and rupture.